Analysis of the impact of tariff preferences on the foreign trade of the Russian Federation and the Republic of Serbia - D. E. Barsegyan (Управление)
The article considers the dynamics and structure of foreign trade of the Russian Federation and the Republic of Serbia, as well as the impact of tariff preferences on foreign trade between two countries. The analysed measures were: dynamics of the Russian Federation’s exports to the Republic of Serbia, dynamics of the Russian Federation’s imports from the Republic of Serbia, tariff preferences applied between countries. The article provides statistical data on the dynamics and structure of foreign trade of the Russian Federation and the Republic of Serbia for 2010–2019 and their dependence on the application of tariff preferences, as well as indicators of trade between the EAEU and the EAEU member states with the Republic of Serbia for 2017–2019. The paper analyses the possible directions of Serbia’s participation in the EAEU and the European Union, assesses the benefits of creating a free trade zone between the EAEU and Serbia, as well as the costs of Serbia’s integration into the European Union. The importance of tariff preferences in the development of foreign trade relations between Russia and Serbia is shown.